Study on Simulation and Calculation of the Regenerative Braking System on Plug-in Hybrid Vehicles - Ngô Quang Thành; Dương Tuấn Tùng (Journal of Technical Education Science, 2025)
The regenerative braking system is designed to convert kinetic energy into electrical energy, which is then reused within the vehicle. In this study, the author develops a mathematical model and designs a regenerative braking system through simulation on a Plug-in Hybrid Electric Vehicle (PHEV) to evaluate its impact on fuel consumption. The simulation is carried out based on the specifications of the Honda CR-V model, utilizing MATLAB Simulink software to perform analysis under various driving conditions, including urban, mixed, and highway driving cycles. The obtained results, including traction power, operating time, generated energy, recovered energy, and energy consumption of both the electric motor and internal combustion engine, indicate that the P-HEV equipped with a regenerative braking system achieves recovered energy levels of 0.72 kWh, 0.33 kWh, and 0.23 kWh in the FPT75, NEDC, and US06 driving cycles respectively. These values demonstrate that the P-HEV is more energy-efficient compared to HEVs and conventional internal combustion engine vehicles, depending on the specific standard driving cycle.